Anti-ganglionic AChR antibodies in Japanese patients with motility disorders - Mukaino, Akihiro; Minami, Hitomi; Isomoto, Hajime; Hamamoto, Hitomi; Ihara, Eikichi; Maeda, Yasuhiro; Higuchi, Osamu; Okanishi, Tohru; Kokudo, Yohei; Deguchi, Kazushi; Sasaki, Fumisato; Ueki, Toshihito; et al. (Journal of gastroenterology, 2018)
Background The existence of several autoantibodies suggests an autoimmune basis for gastrointestinal (GI) dysmotility. Whether GI motility disorders are features of autoimmune autonomic ganglionopathy (AAG) or are related to circulating anti-ganglionic acetylcholine receptor (gAChR) antibodies (Abs) is not known. The aim of this study was to determine the associations between autonomic dysfunction, anti-gAChR Abs, and clinical features in patients with GI motility disorders including achalasia and chronic intestinal pseudo-obstruction (CIPO). Methods First study: retrospective cohort study and laboratory investigation. Samples from 123 patients with seropositive AAG were obtained between 2012 and 2017. Second study: prospective study. Samples from 28 patients with achalasia and 14 patients with CIPO were obtained between 2014 and 2016, and 2013 and 2017, respectively. In the first study, we analyzed clinical profiles of seropositive AAG patients. In the second study, we compared clinical profiles, autonomic symptoms, and results of antibody screening between seropositive, seronegative achalasia, and CIPO groups. Results In the first study, we identified 10 patients (8.1%) who presented with achalasia, or gastroparesis, or paralytic ileus. In the second study, we detected anti-gAChR Abs in 21.4% of the achalasia patients, and in 50.0% of the CIPO patients. Although patients with achalasia and CIPO demonstrated widespread autonomic dysfunction, bladder dysfunction was observed in the seropositive patients with CIPO as a prominent clinical characteristic of dysautonomia. Conclusions These results demonstrate a significant prevalence of anti-gAChR antibodies in patients with achalasia and CIPO. Anti-gAChR Abs might mediate autonomic dysfunction, contributing to autoimmune mechanisms underlying these GI motility disorders.